Pentingnya Pendidikan Kesehatan pada Anak di Pusat Pendidikan Tahfidz Sains dan Teknologi Pulau Penang: Protokol Pengabdian Masyarakat - Trias Mahmudiono; Dominikus Raditya Atmaka; Ratna Dwi Puji Astuti; Damai Arum Pratiwi; Shinta Arta Mulia; Eka Cahya Febrianto; Wan Ismahanisa Ismail; Mohamad Azhar; Mohamad Halim; Muhammad Nabil Fikri (Media Gizi Kesmas, 2024)
Background: Health education plays a vital role in shaping the physical, mental, and social well-being of children by imparting essential knowledge and skills for informed health decisions. Objectives: This paper explores the significance of health education in children, emphasizing its impact on development and effective implementation strategies using hands-on activity. Methods: The community development held at Pusat Pendidikan Tahfidz dan Teknologi Pulau Penang with the title Program Saintis Muda dan Doctor to Be. The program is collaboration initiative of Faculty of Public Health Universitas Airlangga and Faculty of Health Science Universiti Teknologi Mara Malaysia. The program consisted of 8 stations and divided to 16 classes. The program involved 432 students from primary school and high school level. Results: Health education develops essential emotional and social skills needed for managing relationships and emotions effectively. Research underscores that healthy children excel academically and contribute to societal health equity. Hands-on learning methods in health education engage children actively through interactive activities and simulations, enhancing practical skills, critical thinking, and personal relevance. These methods bridge theoretical knowledge with real-world application, empowering children to manage their health effectively. Conclusion: Investing in comprehensive health education programs ensures a healthier and resilient future generation.